Imaging integrin alpha‐v‐beta‐3 expression in tumors with an 18F‐labeled dimeric RGD peptide. (11th January 2013) - Dijkgraaf, Ingrid; Terry, Samantha Y. A.; McBride, William J.; Goldenberg, David M.; Laverman, Peter; Franssen, Gerben M.; Oyen, Wim J. G.; Boerman, Otto C.
Abstract : Integrin α v β 3 receptors are expressed on activated endothelial cells during neovascularization to maintain tumor growth. Many radiolabeled probes utilize the tight and specific association between the arginine–glycine–aspartatic acid (RGD) peptide and integrin α v β 3, but one main obstacle for any clinical application of these probes is the laborious multistep radiosynthesis of 18 F. In this study, the dimeric RGD peptide, E‐[c(RGDfK)]2, was conjugated with NODAGA and radiolabeled with 18 F in a simple one‐pot process with a radiolabeling yield of 20%, the whole process lasting only 45 min. NODAGA‐E‐[c(RGDfK)]2 labeled with 18 F at a specific activity of 1.8 MBq nmol −1 and a radiochemical purity of 100% could be achieved. The log P value of 18 F‐labeled NODAGA‐E‐[c(RGDfK)]2 was −4.26 ± 0.02. In biodistribution studies, 18 F‐NODAGA‐E‐[c(RGDfK)]2 cleared rapidly from the blood with 0.03 ± 0.01 percentage injected dose per gram (%ID g −1 ) in the blood at 2 h p.i., mainly via the kidneys, and showed good in vivo stability. Tumor uptake of 18 F‐NODAGA‐E‐[c(RGDfK)]2 (3.44 ± 0.20 %ID g −1, 2 h p.i.) was significantly lower than that of reference compounds 68 Ga‐labeled NODAGA‐E‐[c(RGDfK)]2 (6.26 ± 0.76 %ID g −1 ; p <0.001) and 111 In‐labeled NODAGA‐E‐[c(RGDfK)]2 (4.99 ± 0.64 %ID g −1 ; p  < 0.01). Co‐injection of an excess of unlabeled NODAGA‐E‐[c(RGDfK)]2 along with 18 F‐NODAGA‐E‐[c(RGDfK)]2 resulted in significantly reduced radioactivity concentrations in the tumor (0.85 ± 0.13 %ID g −1 ). The α v β 3 integrin‐expressing SK‐RC‐52 tumor could be successfully visualized by microPET with 18 F‐labeled NODAGA‐E‐[c(RGDfK)]2 . In conclusion, NODAGA‐E‐[c(RGDfK)]2 could be labeled rapidly with 18 F using a direct aqueous, one‐pot method and it accumulated specifically in α v β 3 integrin‐expressing SK‐RC‐52 tumors, allowing for visualization by microPET. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : In this study the angiogenesis‐targeting dimeric peptide NODAGA‐E‐[c(RGDfK)]2 was labeled with 18 F using a quick, direct, aqueous and one‐pot method. In biodistribution and microPET imaging studies 18 F‐NODAGA‐E‐[c(RGDfK)]2 showed specific uptake in integrin α v β 3 ‐expressing SK‐RC‐52 subcutaneous xenografts in nude BALB/c mice. 18 F‐NODAGA‐E‐[c(RGDfK)]2 showed rapid blood clearance as well as good in vivo stability.